A fluorescent naphthalimide NADH mimic for continuous and reversible sensing of cellular redox state. Issue 15 (30th January 2020) - Sharma, Hemant; Tan, Nian Kee; Trinh, Natalie; Yeo, Jia Hao; New, Elizabeth J.; Pfeffer, Frederick M.
Abstract : A new naphthalimide based NADH mimic that functions as a fully reversible fluorescent "on off" probe for redox state has been synthesised and evaluated. Abstract : A fluorescent, naphthalimide-based, NADH mimic has been synthesised as a reversible, biocompatible, "on–off" probe for the detection of changes in intracellular redox environment (both oxidation and reduction). Interconversion was confirmed by means of electrochemistry and also 1 H NMR, UV-vis and fluorescence spectroscopy. The reversibility was also successfully detected in A549 cells under simulated redox stress.